The effect of anticoagulants in blood collection tubes on Plasmodium falciparum transmission in direct membrane feeding assays. (28th June 2021) - Graumans, Wouter; Lanke, Kjerstin; van Gemert, Geert-Jan; Alkema, Manon; van de Vegte-Bolmer, Marga; Bousema, Teun; Collins, Katharine A
Abstract: Background: Direct membrane feeding assays assess the transmission potential of malaria-infected individuals using whole blood collected in anticoagulant vacutainers. Methods: The potential inhibitory effect of four commonly used anticoagulants on gametocyte infectivity to mosquitoes was assessed in standard membrane feeding assays with cultured Plasmodium falciparum . Results: Infection burden in mosquitoes was significantly reduced when blood was collected in sodium citrate and EDTA. Transmission was highest when blood was collected in lithium heparin and sodium heparin, although a concentration-dependent inhibition of mosquito infection was also observed. Conclusions: Although anticoagulants can reduce transmission efficiency, lithium heparin and sodium heparin are the best anticoagulants for evaluating malaria transmission.